The Duke of Stockbridge - Bellamy, Edward (Saga Egmont, 2023)
\'The Duke of Stockbridge\' (1900) is a classic novel by the American author, Edward Bellamy, most famous for his socialist and utopian novel \'Looking Backward: 2000-1887\' (1888). Written in 1879, this tale, set around Shay\'s Rebellion of 1786 - 1787 and the armed uprising in Western Massachusetts due to the government\'s tax rises, is a compelling story that has the author\'s political ideals at its heart. ´The Duke of Stockbridge´ is a thrilling read and will delight people who are interested in American history.